Difference Table Example - Example for n = 5 j=2 j=1 j=3 j=4 k = 1 f(x1 f(x2)f(x1 x2 x1 = f[x2 x1 f[x3,x2]f[x2,x1 x3 x1 = f[x3 x2 x1

# Difference Table Example - Example for n = 5 j=2 j=1 j=3...

This preview shows page 1 out of 1 page.

Example for n = 5 j = 1 j = 2 j = 3 j = 4 k = 1 f ( x 1 ) -→ f ( x 2 ) - f ( x 1 ) x 2 - x 1 = f [ x 2 , x 1 ] -→ f [ x 3 ,x 2 ] - f [ x 2 ,x 1 ] x 3 - x 1 = f [ x 3 , x 2 , x 1 ] -→ f [ x 4 ,x 3 ,x 2 ] - f [ x 3 ,x 2 ,x 1 ] x 4 - x 1 = f [ x 4 , x 3 , x 2 , x 1 ] % % % k = 2 f ( x 2 ) -→ f ( x 3 ) - f ( x 2 ) x 3 - x 2 = f [ x 3 , x 2 ] -→ f [ x 4 ,x 3 ] - f [ x 3 ,x 2 ] x 4 - x 2 = f [ x 4 , x 3 , x 2 ] -→ f [ x 5 ,x 4 ,x 3 ] - f [ x 4 ,x 3 ,x 2 ] x 5 - x 2 = f [ x 5 , x 4 , x 3 , x 2 ] % % % k = 3 f ( x 3 ) -→ f ( x 4 ) - f ( x 3 ) x 4 - x 3 = f [ x 4 , x 3 ] -→ f [ x 5 ,x 4 ] - f [ x 4 ,x 3 ] x 5 - x 3 = f [ x 5 , x 4 , x 3 ] 0 % % k = 4 f ( x 4 ) -→ f ( x 5 ) - f ( x 4 ) x 5 - x 4 = f [ x 5 , x 4

#### You've reached the end of your free preview.

Want to read the whole page?

• Spring '12
• vasd